THE FOLKLORE TRADITIONS IN THE POETESS ZULFIYA MUMINOVA’S POETRY - Abdujabborova Khilola Rakhmatilla kizi; Kozimova Zumriniso Ismoilovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers the favorite national poetess Zulfiya Muminova’s poetry and its distinctive features as well as her skills of using the folklore. Besides, her works such as “Oq ilon” (white snake) and “Xalq ohanglari” (folk tones) written under the influence of the folklore are analyzed.